Retrospective Evaluation of Radiographic Findings in Patients with Pulmonary Tuberculosis: An Observational Study - Dasrath Wadhwani, Nitin; Bapusaheb Patil, Niranjan (Asian Journal of Medical Radiological Research, 2019)
Background: Tuberculosis remains a worldwide health hazard instead well documented well publicized methods of prevention and cure. Chest radiographs are used to stratify for risk and to assess for asymptomatic active disease. Hence; we planned the present study to retrospectively analyze the data of the pulmonary tuberculosis patients for analyzing the spectrum of radiographic findings. Subjects and Methods: In the present study, we analyzed the data records of a total of 100 pulmonary tuberculosis patients. A self-framed master cart was prepared in which, past medical history, clinical history, radiographic findings, clinical findings of all the patients was obtained. Data records of only those patients were analyzed in which both clinical and bacteriologic confirmation of the disease was present. Radiographs were evaluated. Only preoperative radiographic findings were taken into consideration. Results: The most common radiographic finding was hilar lymph node, found to be present in 66 percent of the patients. Unilateral nodular infiltration was found to be present in 25 percent of the patients. Patchy consolidation was seen in 22 percent of the patients. Fibrotic scar was seen in 10 percent of the patients while calcified nodule was seen in 8 percent of the patients. Conclusion: In diagnosing and assessing the extent of severity among tuberculosis patients, radiographic imaging is a vital tool.